MITRAL VALVE DYSPLASIA TREATMENT (Neo Scientific Peer Reviewed Journal, 2024)
Hemodynamic shifts in patients with mitral valve dysplasia (MVD) were investigated in this article. Forty-seven patients with DMC were examined. Hemodynamic changes in patients with DMC can be characterized as a risk factor for myocardial dystrophy and heart failure. It is recommended to conduct timely complex treatment with obligatory inclusion of immunomodulatory therapy in DMC patients.